Adverse events due to psoriasis treatment - Kokelj, F... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Any treatment can cause some undesired reactions that may be local, systemic, predictable or unpredictable. In the present study we describe our experience concerning the incidence of drug reactions caused by the most common psoriatictreatments. Both topical, vitamin D derivatives and topical retinoids, or systemic, etretinate and cyclosporin A, can cause a large spectrum of adverse reactions that must be known and considered by both doctors and patients in order to obtain the best clinical results. In this paper we summarize our experience with the more common and recent treatments for psoriasis.
Keywords: Adverse effects; Cyclosporine; Drug therapy; Etretinate; Psoriasis; Retinoids; Vitamin d